PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL SIKLUS BELAJAR 5E PADA MATERI HUKUM DASAR KIMIA DALAM MENINGKATKAN HASIL BELAJAR MAHASISWA - Sartika, Rody Putra; Hadi, Lukman (Universitas Tanjungpura, 2015)
The aim of this study was to describe the student’ understanding of law of Fundamental chemistry concept after learning using tools developed through 5E learning cycle model. Designing of learning tools adopted Dick and Carey model. Learning tools was tested on students PGMIPAU FKIP Untan first half of 2014. This type of study was Research and Development. Instruments in this study were the achievement test, observation sheets of lesson plan implementation and observation sheets of barriers in learning. Data were analyzed using qualitative descriptive analysis. The findings of the study were: tools developed had feasible validity, implementation of lesson plan was very good, and students' understanding of law of fundamental chemistry concepts was improved that can be seen from the normalized gain scores. It was concluded that student’ learning outcomes after implementing 5E learning cycle model on the law of fundamental chemistry has increased. Key words :5E learning cycle model, law of fundamental chemistry.